GEOPHYSICAL CHARACTERIZATION OF AQUIFER SYSTEMS USING VERTICAL ELECTRICAL SOUNDING METHOD IN DEMSA, NORTHEAST NIGERIA - Babagana, Saleh Mustapha; Sharma, Satendra (International Journal of Research -GRANTHAALAYAH, 2020)
Electrical resistivity method using vertical electrical sounding (VES) technique and Schlumberger array was employed with the aim of delineating limits and types of aquifer system(s), and stratigraphic composition of the Demsa area, a confluence of Benue River in Northeast Nigeria. The result revealed that the hydrogeology of the area may be controlled by fractures (secondary porosity) developed in sedimentary units. Two aquifers, namely the upper alluvial aquifer and the confined deeper aquifer systems exist in the study area. The two aquifers occur at depths of 20.5 – 41 m, and 43.8 – 78.9 m respectively, and are separated by a thin layer of poorly permeable clays and silts, ranged between 1.1 – 5.3 m in thickness. The lateral extent of the aquifer systems extend almost evenly across the area. The aquifers’ thickness tends to decrease with increase in distance of VES station from the Benue River which suggested that the aquifer systems are probably recharged by direct escapement of the Benue River.